SPEECH ACTS IN STUDENTS PODCAST: PRAGMATIC INSIGHTS FOR EFL TEACHING - purnamasari, jelita; Agustiani, Rahmah; Haz, Musdalifah (LPPM UM Metro, 2025)
This study examined the use of speech acts in student-produced podcasts to explore how English as a Foreign Language learners developed pragmatic competence in authentic communication. The research was motivated by the gap between classroom instruction and students’ ability to use English appropriately in real contexts. The objective was to identify the types of speech acts employed, analyze their communicative functions, and highlight pedagogical implications. A qualitative descriptive approach with discourse analysis was applied. Data consisted of two podcasts produced by second-semester Communication Science students at IISIP YAPIS Biak, Papua. The recordings were transcribed, segmented into utterances, and coded according to Searle’s five categories of speech acts. To support interpretation, frequencies and percentages were calculated descriptively to show the relative dominance of each type. The findings revealed that representatives, directives, and expressives were most frequently used, while commissives were rare and declarations were absent. Students used speech acts strategically to open and close interactions, guide questioning, elaborate on ideas, and build rapport. The study concluded that podcast production provided a meaningful platform for practicing pragmatic competence, allowing students to balance formality and informality, sustain interaction, and develop interpersonal awareness. The findings implied that integrating podcasts into language learning can enrich communicative practice and bridge classroom learning with authentic use of English.